Effect of Contact Geometry on the Contact Stresses in a Flat with Round Edge Contact (Fracture and Structural Integrity, 2019)
The blade-disc dovetail interface in an aero-engine compressor is characterized by a non-uniform pressure distribution which can be obtained by an equivalent flat with round edge-on-plate configuration. The contact tractions for a mating pair are affected by many parameters which include, contact geometry, loading conditions, and material properties; with contact geometry being one of the prominent factors. In the present work, a 2-D elastic and elasto-plastic finite element analysis has been carried out for a rounded contact geometry to study the influence of the radius of the corners ‘R’ and length of the flat region ‘2a’. It is observed that the peak tensile stress in the fretting direction was found to decrease with increasing ‘a’ (for constant ‘R’) which is likely to delay the crack initiation. Also, as compared to elasto-plastic analysis, elastic analysis overestimates peak tensile stress and possibly give a conservative estimate for the fretting fatigue life. Further, the effect of modelling elastic-plastic behaviour is significant for low a/R ratio (for constant ‘R’). However, opposite trend was observed when ‘R’ was varied keeping ‘a’ constant. Also, it is found that the effect of contact geometry cannot be characterized using a single parameter like a/R ratio or contact area.
Keywords: Dovetail; Flat with rounded edge; Fretting; Contact geometry